Non invasive imaging of coronary arteries with 64-slice CT and 1.5T MRI: challenging invasive techniques - Cademartiri, F.; Palumbo, A.A.; Maffei et al., E. (Acta Biomedica Atenei Parmensis, 2007)
Non-invasive coronary artery imaging challenges any diagnostic modality, because of the complex and tortuous anatomy and cardiac contraction and respiration. Therefore, non-invasive coronary imaging requires high spatial and temporal resolution. Our purpose is to discuss the feasible applications in coronary imaging of Magnetic Resonance Imaging and Multi-slice Computed Tomography (MSCT). Focus will be devoted to potential indications and clinical impact of MSCT because of the fast development and the important results recently reported, in particular with the recent introduction of 64-slice equipments. MSCT of the coronary arteries is a promising imaging modality for the assessment of coronary lumen and wall.